Der Gnadenstreit: Luis de Molina - Grössl, Johannes (Der Glaube im Denken. Eine Philosophiegeschichte)

The Impeccable Freedom of Christ - Grössl, Johannes (Theological Perspectives on Free Will: Compatibility, Community, Christology)

Zu den Anforderungen einer musikalischen Stilometrie - Kepper, Johannes
This is the extended abstract for my conference paper from the 2020 DHd Conference in Paderborn, along with the slides and moderator notes from the corresponding presentation.

DomesticBeethoven/bith-annotator: Release 2023-04 - Kepper, Johannes
This release covers the state of this prototype app at the end of the funding phase for the Paderborn University part of the Beethoven in the House project. It uses https://api.domestic-beethoven.eu/ld/BithCollection.jsonld as starting point for traversing the LOD graph, and reads data from the project pod available from https://bith.solidcommunity.net/public/bith.ttl (which has no content at the time of the release).
Keywords: MEI; Edirom; Music Encoding Initiative; Linked Open Data; MELD

MEI: The Music Encoding Initiative Guidelines (PDF)
PDF versions of the Music Encoding Initiative Guidelines 5.0 [2023]: This version represents the 5.0 release of the Music Encoding Initiative Guidelines.

Beethoven in the House: Selective Encodings of Arrangements of Beethoven’s opp. 91, 92, and 93. - Rosendahl, Lisa
This dataset contains selective MEI encodings of a number of arrangements of Beethoven’s Opp. 91, 92, and 93. These encodings were prepared in the context of the Beethoven in the House project, jointly funded by AHRC and DFG from 2020 to 2023. It is a slight update on v1.0.0 in better organizing the release assets.
Keywords: BitH; Dataset; Domestic Music Arrangements; Ludwig van Beethoven; MEI; Music Encoding Initiative

A New Conceptual Model for Musical Sources and Musicological Studies - Shibata, Elisabete; Lewis, David; Saccomano, Mark; Kepper, Johannes; Page, Kevin (Proceedings of the Music Encoding Conference 2022)
We present a new multi-layered, conceptual model for associating musical source materials to musicological arguments. We describe our proposal for operationalizing these concepts through a framework for musical annotation which we have implemented using RDF. Briefly stated, this model shows how portions of digitized data in various files and formats can be identified, selected, labelled, and compared.
Keywords: BitH; Linked Data

Supporting Musicological Investigations With Information Retrieval Tools: An Iterative Approach to Data Collection - Lewis, David; Shibata, Elisabete; Hankinson, Andrew; Kepper, Johannes; Page, Kevin R.; Rosendahl, Lisa; Saccomano, Mark; Siegert, Christine
Digital musicology research often proceeds by extending and enriching its evidence base as it progresses, rather than starting with a complete corpus of data and metadata, as a consequence of an emergent research need. In this paper, we consider a research workflow which assumes an incremental approach to data gathering and annotation. We describe tooling which implements parts of this workflow, developed to support the study of nineteenth-century music arrangements, and evaluate the applicability of our approach through interviews with musicologists and music editors who have used the tools. We conclude by considering extensions of this approach and the wider implications for digital musicology and music information retrieval.
Keywords: BitH; Linked Data

Temporal Sorting of Optical Multiwave-Mixing Processes in Semiconductor Quantum Dots - Grisard, Stefan; Trifonov, Artur V.; Rose, Hendrik; Reichhardt, Rilana; Reichelt, Matthias; Schneider, Christian; Kamp, Martin; Höfling, Sven; Bayer, Manfred; Meier, Torsten; Akimov, Ilya A. (ACS Photonics)

Review of: Open Citizen Science: fostering open knowledge with participation. - Mauermeister, Sylvi (Research Ideas and Outcomes)

Expertise and professionalism for inclusive (mathematics) teaching and learning: reflections on findings from interdisciplinary professionalisation research - Seitz, Simone; Häsel-Weide, Uta; Wilke, Yannik; Wallner, Melina (Teachers and Teaching)
Keywords: Arts and Humanities (miscellaneous); Education

Methodenentwicklung zur Verbesserung der Schädigungsmodellierung in der numerischen 3D-Belastungssimulation mechanischer Fügeverfahren unter Berücksichtigung der fügeinduzierten Vorbeanspruchung - Rossel, Moritz Sebastian; Meschut, Gerson; Bielak, Christian Roman; Otroshi, Mortaza

Geschichte der italienischen Zuwanderung nach Belgien im Medium Comic: Macaroni! (2016) und Une histoire importante. 70 ans d’immigration italienne en Belgique et plus (2019) - Schmitz, Sabine (Letteratura e migrazione/Literatur und Migration. Proposte intorno alla figura del ponte/ Fragen zur Figur der Brücke)

Lo fantástico en la escena del crimen: análisis del proceso de adaptación de la historieta El hipnotizador (2007) de Pablo de Santis y Juan Sáenz Valiente a la serie televisiva homónima de HBO Latin América (2015) - Schmitz, Sabine (Inter/Transmedialidad en el género negro y policial latinoamericano)

Phantastik in Belgien: Erzählungen von Franz Hellens und Thomas Gunzig über Doppelgänger, Monster und Kuhfräulein - Schmitz, Sabine; Schädlich, Birgit (Belgien – anregend anders. Fachwissenschaft und Fachdidaktik untersuchen die Vielfalt der Sprachen, Literaturen und Kulturen in Belgien)

Brückenbau oder Steg der Erinnerung? Narrationen zur italienischen Arbeitsmigration des 20. Jahrhunderts im aktuellen belgischen Comic - Schmitz, Sabine (Letteratura come ponte? Littérature comme pont? Literatur als Brücke? Zur Frage von Migration und Literatur)

Prólogo - Schmitz, Sabine; Verdú Schumann, Daniel (Inter/Transmedialidad en el género negro y policial latinoamericano)

Belgien – anregend anders. Fachwissenschaft und Fachdidaktik untersuchen die Vielfalt der Sprachen, Literaturen und Kulturen in Belgien

Inter/Transmedialidad en el género negro y policial latinoamericano

Digitale Desökonomie: Unproduktivität, Trägheit und Exzess im digitalen Milieu - Althoff, Sebastian
Die Warnung von Eltern, aufzupassen, was man online teilt, ist allgegenwärtig. Dem schließen sich Datenschützer*innen an und gebieten einen bewussten und sparsamen Umgang mit Diensten und Daten. Eine digitale Desökonomie widersetzt sich diesen Warnungen und sucht den kritischen Umgang mit der digitalen Gegenwartskultur nicht in der Askese, sondern im Exzess. Kunstwerke, Bilder und Daten sind »zu viel«, türmen sich auf und wiederholen sich ständig. Mit Bezug auf Ansätze der Gouvernementalität, der Queer Theory und auf Theorien von Georges Bataille und Roger Caillois analysiert Sebastian Althoff diese unproduktive Produktionsweise des Digitalen und zeigt eine Praxis auf, die Trägheit statt flow schafft.